2012
DOI: 10.1590/s0011-52582012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Transições ocupacionais e mercados de trabalho intermetropolitanos: os casos de Rio de Janeiro e São Paulo

Abstract: E m 1994 as regiões metropolitanas (RM) do Rio de Janeiro e de São Paulo registraram perto de 3.5 milhões de eventos de emprego formal. Isso não quer dizer que foram criados 3.5 milhões de empregos no período, nem que 3.5 milhões de pessoas se empregaram formalmente 1 . Uma mesma pessoa pode ter tido vários empregos formais, e um mesmo posto de trabalho pode ter sido ocupado por mais de uma pessoa ao longo do tempo. Aquela cifra quer apenas dizer que os postos de trabalho existentes, os que foram criados e os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…Turnover is a critical factor to the organizations, to individuals and to the society and presents both positive and negative aspects (Phillips and Connell, 2003). Although there are studies of turnover in the last 30 years in behavioral area and human resources with theories about voluntary resignation (Tett and Meyer, 1993; Mobley, 1992; Lee and Mowday, 1987; Dalton and Todor, 1979; Burguess et al , 2001), such as in labor economics area (Du et al , 2006; O’Higgins, 2012), in Brazil they were identified as efforts with works of Pinto and Gonzaga (2014) and Cardoso and Lage (2007). However, the turnover in Brazil still has gaps in academic research agenda (Campos and Malik, 2008; Menezes and Bastos, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Turnover is a critical factor to the organizations, to individuals and to the society and presents both positive and negative aspects (Phillips and Connell, 2003). Although there are studies of turnover in the last 30 years in behavioral area and human resources with theories about voluntary resignation (Tett and Meyer, 1993; Mobley, 1992; Lee and Mowday, 1987; Dalton and Todor, 1979; Burguess et al , 2001), such as in labor economics area (Du et al , 2006; O’Higgins, 2012), in Brazil they were identified as efforts with works of Pinto and Gonzaga (2014) and Cardoso and Lage (2007). However, the turnover in Brazil still has gaps in academic research agenda (Campos and Malik, 2008; Menezes and Bastos, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Parmi les rares exceptions récentes, citonsMarques et al (2008) et Cardoso (2012 Voir par exemple le livre Cidade Partida du journaliste ZuenirVentura (1994), qui a été un grand succès de librairie.6 Attribuée le plus souvent à Gilberto Freyre dans son oeuvre maîtresse, Casa Grande etSenzala, 1933. Antonio Sergio Guimarrães a souligné que si cette oeuvre a bien inspiré cette théorie, le mot même n'y figure pas et n'a été employé que tardivement par Freyre(Guimarrães, 2001).…”
unclassified
“…For example, a firm is fined about one minimum wage for each worker that is found unregistered, or the firm can be fined up to a third of a minimum wage per employee if it does not comply with mandatory contributions to the severance fund (ALMEIDA; CARNEIRO, 2012). 1.2.5 On the other hand, it is a well-known fact that compliant (formal) firms are those more visible to labor inspectors and thus subject to more inspections whereas informal firms are smaller and thus difficult to get caught (CARDOSO; LAGE, 2006). There are also other expected costs for formal firms associated with labor courts in case the worker is fired and decides to file a lawsuit against the firm.…”
Section: Labor Markets In Brazilmentioning
confidence: 99%